Children’s humoristic utterances in focus: Pragmatic, cognitive and social implications - Ré, Alessandra Del [UNESP]; Dodane, Christelle; Morgenstern, Aliyah (GN1 Sistemas e Publicacoes, 2019)
In order to understand how children learn to recognize and use humor in their speech, we have chosen to study their linguistic production in two different languages and cultures: a French-speaking monolingual child and a Brazilian Portuguese-speaking child, video-recorded once a month in a longitudinal study, whose data were analyzed for this article between 24 and 42 months. The results of the multimodal linguistic coding of our data enabled us to describe the paths the two children followed to get from first instances of shared amusement initiated by the adult to their own verbal production of successful humor in dialogue. The different parameters required for humor are set from the age of 2;4 years old. Our study demonstrates that the production of children’s humor is closely linked to the family input and to children’s multimodal linguistic and meta-cognitive development. We did not observe important differences between the two children at the macro-cultural level, but there were some inter-individual differences.
ENUNCIADOS HUMORISTICOS INFANTIS EM FOCO: IMPLICAÇÕES PRAGMATICAS, COGNITIVAS E SOCIAIS1
Keywords: Child; Cognitive; Humor; Pragmatic; Social